Reconstruction Of Community Economic Empowerment Based on Religious Philanthropy: A Comparative Analysis of Zakat and Tithes - Samsul Mu'arif; Ambarwati (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
Abstract Economic empowerment of the community is a goal of the teachings including Islam and Christianity. In Islam, zakat serves as an obligatory form of worship with strategic socio-economic dimensions, as emphasized in At-Taubah:103. Meanwhile, in the Christian tradition, tithing is a religious obligation deeply rooted in the Old Testament (Leviticus 27:30–31) and continues to enjoy moral legitimacy in the New Testament. This article aims to analyze the concept and practice of economic empowerment through zakat and tithing, placing them within the framework of community economic empowerment. This research uses qualitative approach with a literature review method that emphasizes philosophical, theological, and conceptual analysis of primary and secondary sources. The results show that zakat contributes significantly to economic empowerment by increasing the independence of MSMEs, strengthening social institutions, developing business partnerships, and providing educational and business capacity development assistance. Meanwhile, tithing serves as a source of church funds with the potential to improve the economic welfare of congregations through business capital assistance, social infrastructure development, strengthening economic networks, and providing support to the congregation. These findings confirm that despite differing theologically and through distribution mechanisms, zakat and tithing share a common orientation: promoting the independence and well-being of the community.   Keywords: Economic empowerment, zakat, tithing, community welfare